Analisis kerusakan sistem papi berbasis solar cell di bandara douw aturure nabire - Fuji Ismatul Rahma; Yenni Arnas; Nurhedhi Desryanto (Yayasan Baru Haji Samsudin, 2026)
The background of this study is the frequent damage to the solar cell-based Precision Approach Path Indicator (PAPI) system at Douw Aturure Nabire Airport, while this system is the only visual landing aid used. This condition has the potential to disrupt the operational reliability of the airport and flight safety, especially during the approach and landing of aircraft. The purpose of this study is to analyze the causes of damage to the solar cell-based PAPI system and compare its reliability with the conventional PAPI system that uses a Constant Current Regulator (CCR). The method used is a descriptive method with a survey approach through field observations, technical measurements, technician interviews, and documentation studies. The data were analyzed descriptively and using a fishbone approach to identify the factors causing the damage, as well as a comparative analysis between the solar cell PAPI and CCR PAPI systems. The discussion of the research includes the performance of solar panels, batteries, inverters, and PAPI lights, the patterns of damage that occurred, and a comparison of the reliability, energy sources, and frequency of interference between the solar cell and CCR systems. The conclusion of the study shows that solar cell-based PAPI systems have a lower reliability level than CCR-based PAPI systems due to power supply instability and environmental influences, thus requiring improved maintenance and system evaluation to support flight safety